Lithium secondary battery

The use of coated lithium nickel metal oxide particles on the positive electrode surface addresses structural deformation in lithium secondary batteries, improving lifespan and capacity by minimizing gliding and crystal structure changes.

KR103043578B1Active Publication Date: 2026-11-05SK ON CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020240164349
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2026-11-05
Estimated Expiration
2044-11-18

Smart Images

  • Figure 112024126644856-PAT00010_ABST
    Figure 112024126644856-PAT00010_ABST
Patent Text Reader

Abstract

A lithium secondary battery according to the present disclosure comprises a positive electrode and a negative electrode facing the positive electrode. The gliding step of the positive electrode is 20 nm or less. The gliding step is defined as the distance between a pair of parallel lines with a non-zero slope that can include two or more of the peak shapes observed in a line scan graph obtained using an atomic force microscope (AFM) of the surface of the positive electrode in a fully discharged state after 500 charge-discharge cycles of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present disclosure provides a positive electrode active material for a secondary battery, a positive electrode for a secondary battery, and a lithium secondary battery. Background Technology

[0003] Rechargeable batteries are batteries capable of repeated charging and discharging, and with the advancement of the information and communication and display industries, they are widely applied as power sources for portable electronic communication devices such as camcorders, mobile phones, and laptop PCs. Furthermore, recently, battery packs containing rechargeable batteries are being developed and applied as power sources for eco-friendly vehicles, such as hybrid cars.

[0004] Examples of lithium secondary batteries include lithium secondary batteries, nickel-cadmium batteries, and nickel-hydrogen batteries; among these, lithium secondary batteries are being actively developed and applied due to their high operating voltage and energy density per unit weight, as well as advantages in charging speed and weight reduction.

[0005] For example, a lithium secondary battery may include an electrode assembly comprising a positive electrode, a negative electrode, and a separator, and an electrolyte impregnating the electrode assembly. The lithium secondary battery may further include an outer casing, for example, in the form of a pouch, that accommodates the electrode assembly and the electrolyte.

[0006] Since it is desirable for lithium-ion batteries to possess high capacity, stability, and long lifespan characteristics, methods have been proposed to introduce single-particle active materials or to control the composition of the active material layer. However, as the structure of the active material deforms during charging and discharging, significantly reducing battery capacity, there was a need to propose a high-capacity cathode with sufficient long lifespan characteristics. The problem to be solved

[0008] One objective of the present disclosure is to provide a lithium secondary battery having improved electrochemical properties. means of solving the problem

[0010] A lithium secondary battery according to the present disclosure comprises a positive electrode and a negative electrode facing the positive electrode. The gliding step of the positive electrode is 20 nm or less. The gliding step is defined as the distance between a pair of parallel lines with a non-zero slope that can include two or more of the peak shapes observed in a line scan graph obtained using an atomic force microscope (AFM) of the surface of the positive electrode in a fully discharged state after 500 charge-discharge cycles of the battery.

[0011] According to exemplary embodiments, the gliding step of the anode may be 10 nm or less.

[0012] According to exemplary embodiments, the positive electrode may include a positive current collector and a positive active material layer disposed on one side of the positive current collector. The positive active material layer may include coated particles. The coated particles may include a core and at least one metal oxide particle. The core may include a lithium nickel metal oxide having a layered structure and may have a single particle structure. The metal oxide particle may be disposed on the surface of the core.

[0013] According to exemplary embodiments, the average particle size (D50) of the metal oxide particles may be 100 nm to 450 nm.

[0014] According to exemplary embodiments, the metal oxide particles may be arranged in an island shape on the surface of the core.

[0015] According to exemplary embodiments, the metal oxide particles may have a spinel crystal structure, a perovskite crystal structure, a garnet crystal structure, or a nasicon crystal structure.

[0016] According to exemplary embodiments, the metal oxide particles may comprise at least one selected from the group consisting of Co, Ba, Ti, Sr, Li, La, Zr, Al, Y, W, and P.

[0017] According to exemplary embodiments, the content of the metal oxide particles may be 500 ppm to 3000 ppm of the total weight of the coated particles.

[0018] According to exemplary embodiments, the content of nickel in the total moles of elements excluding lithium and oxygen in the lithium nickel metal oxide may be 60 mol% to 99 mol%.

[0019] According to exemplary embodiments, the average particle size (D50) of the core may be 1 μm to 10 μm.

[0020] According to exemplary embodiments, the grain size of the core may be 200 nm to 600 nm.

[0021] A positive electrode for a secondary battery according to the present disclosure comprises a positive current collector; and a positive active material layer disposed on one surface of the positive current collector. The positive active material layer comprises a positive active material for the secondary battery.

[0022] A lithium secondary battery according to the present disclosure comprises: the positive electrode; and a negative electrode facing the positive electrode. Effects of the invention

[0024] The positive electrode active material for a secondary battery according to the exemplary embodiments of the present disclosure may exhibit minimal deformation of the crystal structure and shape of the particles even during repeated charging and discharging of the battery. Furthermore, the positive electrode active material for a secondary battery may have a high capacity. Accordingly, the lifespan characteristics of a high-capacity battery may be improved.

[0025] The positive electrode for a secondary battery and the lithium secondary battery including the same according to exemplary embodiments of the present disclosure may have a high capacity while having a small decrease in capacity during repeated charging and discharging.

[0026] The cathode for a secondary battery and the lithium secondary battery including the same disclosed in the present disclosure can be widely applied in green technology fields such as electric vehicles, battery charging stations, and other solar power generation and wind power generation utilizing batteries. Furthermore, the cathode for a secondary battery and the lithium secondary battery including the same disclosed in the present disclosure can be used in eco-friendly electric vehicles, hybrid vehicles, etc., to prevent climate change by suppressing air pollution and greenhouse gas emissions. Brief explanation of the drawing

[0028] FIGS. 1 and FIGS. 2 are a schematic plan view and a cross-sectional view, respectively, showing a lithium secondary battery according to exemplary embodiments. FIG. 3 is a schematic diagram of a cross-section of a coated particle according to an exemplary embodiment of the present disclosure. Figure 4 is a schematic diagram of a cross-section of a conventional positive active material particle after charging and discharging. FIG. 5 is a schematic diagram of a cross-section of a coated particle according to an exemplary embodiment of the present disclosure after charging and discharging. Figure 6 is a scanning electron microscope (SEM) image of the coated particles of Example 1. Figure 7 is a scanning electron microscope (SEM) image of the coated particles of Comparative Example 2. Figure 8a is an AFM image of the anode after repeated charge and discharge of Example 2. FIG. 8b is a step difference graph according to line scanning of the anode after repeated charge and discharge of Example 2, scanned along the dotted line of FIG. 8a. Figure 9a is an AFM image of the anode after repeated charge and discharge of Comparative Example 2. Figure 9b is a step difference graph according to line scanning of the anode after repeated charge and discharge of Comparative Example 2, scanned along the solid line of Figure 9a. Specific details for implementing the invention

[0029] According to exemplary embodiments of the present disclosure, a positive electrode active material for a secondary battery is provided, comprising coated particles having metal oxide particles on a core surface. Additionally, a positive electrode for a secondary battery according to an exemplary embodiment of the present disclosure comprises said positive electrode active material for a secondary battery. A lithium secondary battery according to an exemplary embodiment of the present disclosure comprises said positive electrode.

[0030] The term “average particle size (D50)” as used in this specification is the average particle size of a plurality of particles, and D50 may be the average particle size obtained as a point corresponding to 50% of the cumulative volume distribution of manufactured active material particles.

[0031] The method for measuring the volumetric cumulative distribution of the above particles is not particularly limited, but can be measured using a laser diffraction particle size analyzer, for example, a Malvern 3000 device can be used.

[0032] Hereinafter, the present disclosure will be described in detail with reference to the attached drawings. However, this is merely illustrative and the present disclosure is not limited to the specific embodiments described illustratively.

[0033] A lithium secondary battery according to exemplary embodiments comprises the positive electrode described above and a negative electrode facing the positive electrode. The lithium secondary battery may include a separator interposed between the positive electrode and the negative electrode, and an electrolyte.

[0034] Hereinafter, a lithium secondary battery according to exemplary embodiments will be described in more detail with reference to the drawings. FIGS. 1 and FIGS. 2 are a schematic plan view and a cross-sectional view, respectively, showing a lithium secondary battery according to exemplary embodiments. For example, FIGS. 2 is a cross-sectional view cut along line II' of FIGS. 1.

[0035] Referring to FIGS. 1 and 2, a lithium secondary battery may include an electrode assembly comprising a positive electrode (100), a negative electrode (130), and a separator (140) interposed between the positive electrode and the negative electrode. The electrode assembly may be accommodated in a case (160) together with an electrolyte and impregnated by the electrolyte.

[0036] The positive electrode (100) includes a positive electrode current collector (105) and a positive electrode active material layer (110), and the positive electrode active material layer (110) may include a positive electrode active material.

[0037] The positive current collector (105) may include, for example, stainless steel, nickel, aluminum, titanium, copper, or an alloy thereof, and may include, for example, aluminum or an aluminum alloy.

[0038] The positive active material layer (110) may be disposed on at least one surface of the positive current collector (105). For example, the positive active material layer (110) may be disposed on one or both surfaces of the positive current collector (105).

[0039] The above positive active material may include coated particles.

[0040] FIG. 3 is a schematic diagram of a cross-section of a coated particle according to an exemplary embodiment of the present disclosure.

[0041] Referring to FIG. 3, the coated particles may include a core (10) and metal oxide particles (20) disposed on the surface of the core (10).

[0042] The core (10) may include a lithium nickel metal oxide. The lithium nickel metal oxide may further include at least one of cobalt (Co), manganese (Mn), and aluminum (Al) in addition to nickel.

[0043] According to exemplary embodiments, the lithium nickel metal oxide may include nickel and manganese. Accordingly, the battery can be increased in capacity while improving the lifespan stability of the battery.

[0044] According to exemplary embodiments, the content of nickel in the total moles of elements excluding lithium and oxygen in the lithium nickel metal oxide may be 60 mol% to 99 mol%.

[0045] Within the above range, the increase in internal resistance due to changes in the crystal structure of the positive electrode active material during rapid charging and discharging of the battery can be reduced without significantly reducing the capacity of the positive electrode.

[0046] According to exemplary embodiments, the lithium nickel metal oxide may comprise a layered structure represented by the following chemical formula 1.

[0047] [Chemical Formula 1]

[0048] Li x Ni a M b O 2+z

[0049] In Chemical Formula 1, 0.9≤x≤1.2, 0.6≤a≤0.99, 0.01≤b≤0.4, and -0.5≤z≤0.1 may be used. As described above, M may include Co, Mn, and / or Al.

[0050] The chemical structure represented by Chemical Formula 1 represents the bonding relationships contained within the layered or crystal structure of the positive electrode active material and does not exclude other additional elements. For example, M includes Co and / or Mn, and Co and / or Mn may be provided as the main active element of the positive electrode active material together with Ni. Chemical Formula 1 is provided to express the bonding relationships of the main active elements and should be understood as encompassing the introduction and substitution of additional elements.

[0051] In one embodiment, auxiliary elements may be further included to enhance the chemical stability of the anode active material or the layered structure / crystal structure by adding to the main active element. The auxiliary elements may be incorporated together within the layered structure / crystal structure to form bonds, and in this case, it should be understood that they are also included within the range of the chemical structure represented by Chemical Formula 1.

[0052] The above auxiliary element may include, for example, at least one of Na, Mg, Ca, Y, Ti, Hf, V, Nb, Ta, Cr, Mo, W, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Sn, Sr, Ba, Ra, P, or Zr. The above auxiliary element may also act as an auxiliary active element that contributes to the capacity / output activity of the cathode active material together with Co or Mn, such as Al.

[0053] For example, the lithium nickel metal oxide may include a layered structure or a crystal structure represented by the following chemical formula 1-1.

[0054] [Chemical Formula 1-1]

[0055] Li x Ni a M1 b1 M2 b2 O 2+z

[0056] In Chemical Formula 1-1, M1 may include Co, Mn and / or Al. M2 may include the auxiliary element described above. In Chemical Formula 1-1, 0.9≤x≤1.2, 0.3≤a≤0.8, 0.01≤b1≤0.4, 0≤b2≤0.1, and -0.5≤z≤0.1.

[0057] The lithium nickel metal oxide may further include a coating element or a doping element. For example, elements substantially identical or similar to the auxiliary elements described above may be used as coating elements or doping elements. For example, any of the elements described above may be used alone or in combination of two or more as coating elements or doping elements.

[0058] The coating element or doping element may be present on the surface of the lithium nickel metal oxide particles or penetrate through the surface of the lithium metal composite oxide particles and be included within the bonding structure represented by Formula 1 or Formula 1-1.

[0059] According to exemplary embodiments, the core (10) may have a single particle structure. As used herein, the term “single particle structure” is used to exclude secondary particles formed by the aggregation of, for example, a plurality of primary particles (e.g., more than 10) into substantially one particle.

[0060] For example, the core (10) is substantially composed of particles in the form of single particles, and a secondary particle structure in which primary particles are assembled or aggregated may be excluded. Also, the term “single particle structure” as used herein does not exclude, for example, 2 to 10 single particles being attached or closely bonded to each other to form a monolithic form.

[0061] The above single particle structure may include a structure in which multiple primary particles are merged together as a single unit and substantially converted into a single particle form.

[0062] For example, the core (10) may have a single-grain structure containing 10 or fewer crystal grains.

[0063] For example, the core (10) may have a single crystal structure. The single crystal structure may include a structure in which a single particle is composed of a single crystal grain. For example, the single crystal structure may be distinguished based on an ion image obtained by analyzing a cross-section of the particle using a Focused Ion Beam (FIB). For example, if the particle has a single crystal structure, a single crystal may be observed in the FIB analysis image according to the difference in crystal orientation.

[0064] According to exemplary embodiments, the average particle size (D50) of the core (10) may be 1 μm to 10 μm. According to some embodiments, the average particle size (D50) of the core (10) may be 2 μm to 5 μm.

[0065] Within the above range, the stability of the positive electrode can be improved, and the durability of the positive electrode may not decrease during repeated charging and discharging of the battery.

[0066] According to exemplary embodiments, the grain size of the core (10) may be 200 nm to 600 nm. According to some embodiments, the grain size of the core (10) may be 200 nm to 400 nm.

[0067] For example, the grain size of the core (10) can be measured by X-ray diffraction (XRD) analysis. According to exemplary embodiments, the grain size can be calculated using the following Scherrer equation, Equation 1, by using the full width at half maximum (FWHM) of the peak corresponding to the crystal plane (104) in the XRD pattern obtained from the XRD analysis of the core (10).

[0068] [Equation 1]

[0069]

[0070] In Equation 1, L represents the grain size, λ the X-ray wavelength, β the full width at half maximum of any peak, and θ the diffraction angle.

[0071] For example, the above XRD analysis is performed on dried powder of lithium metal oxide particles using Cu Kα rays as a light source, 10 o to 120 o In the range of diffraction angle (2θ), 0.0065 o It can be performed at a scan rate of / step.

[0072] The above lithium nickel metal oxide may have a layered structure. The layered structure allows a large amount of lithium ions to be inserted between the two-dimensional layers, thereby increasing the capacity of the anode.

[0073] Figure 4 is a schematic diagram of a cross-section of a conventional positive active material particle after charging and discharging.

[0074] Referring to FIG. 4, when a battery containing a positive electrode active material including the lithium nickel metal oxide is charged, lithium may be inserted unevenly between the layers. Accordingly, interlayer slippage, such as gliding, may occur, and consequently, irregularities may be formed on the surface of the charged positive electrode active material, and the shape of the positive electrode active material may not be fully and reversibly restored after discharge.

[0075] When the above-mentioned battery is repeatedly charged and discharged, damage such as cracks may occur around the area where the gliding phenomenon has occurred. Consequently, the layered structure may irreversibly change into a rock salt structure. The gliding phenomenon may occur particularly more when the positive electrode active material has a single-particle structure.

[0076] FIG. 5 is a schematic diagram of a cross-section of a coated particle according to an exemplary embodiment of the present disclosure after charging and discharging.

[0077] The coated particles according to the present disclosure may include at least one metal oxide particle (20) disposed on the surface of a core (10) comprising a lithium nickel metal oxide having a layered structure. Accordingly, the formation of a step difference due to gliding of the metal oxide particle (20) can be suppressed, and cracks and changes in the crystal structure of the positive active material particle due to gliding phenomena can be prevented even during repeated charging and discharging.

[0078] The metal oxide particles (20) may have an average particle size (D50) of 100 nm to 450 nm. According to exemplary embodiments, the average particle size (D50) of the metal oxide particles (20) may be 200 nm to 400 nm, 210 nm to 350 nm, or 220 nm to 300 nm.

[0079] Within the above range, gliding phenomena caused by the layered structure of lithium nickel metal oxide can be suppressed, the durability of the positive electrode active material can be improved, and the lifespan characteristics of the battery can be improved.

[0080] If the average particle size (D50) of the metal oxide particles (20) is less than 100 nm, the particle size of the metal oxide particles (20) is not sufficiently large to the step where gliding occurs, so the occurrence of the step may not be suppressed (e.g., see FIG. 4). Accordingly, the battery life characteristics may deteriorate.

[0081] If the average particle size (D50) of the metal oxide particles (20) exceeds 450 nm, the volume of the metal oxide particles (20) on the outer surface of the core (10) is large, so the density of the positive active material in the positive active material layer may be relatively reduced, and the coated portion with large particles may act as resistance during lithium insertion / extraction. Accordingly, the energy density and capacity of the positive may be reduced.

[0082] According to exemplary embodiments, metal oxide particles (20) may be arranged in an island shape on the surface of the core. The "island shape" is a concept distinct from a coating in the form of a continuous layer, and the plurality of metal oxide particles (20) may not be arranged entirely on the surface of the core (10).

[0083] For example, a plurality of metal oxide particles (20) may be placed on at least a portion of the surface of the core (10). For example, a plurality of metal oxide particles (20) may be placed in two or more areas of the surface of the core (10) that are spaced apart from each other.

[0084] Accordingly, a pathway for the movement of lithium ions is secured, allowing for smooth insertion and extraction between the layered structures.

[0085] According to exemplary embodiments, the metal oxide particles (20) may have a spinel crystal structure, a perovskite crystal structure, a garnet crystal structure, or a nasicon crystal structure. The metal oxide particles (20) may include an oxide-based solid electrolyte, and thus the lithium ion conductivity and / or electrical conductivity of the anode containing the coated particles may not be reduced.

[0086] According to exemplary embodiments, the metal oxide particles (20) may include Co, Ba, Ti, Sr, Li, La, Zr, Al, Y, W, and P, etc. For example, the metal oxide particles (20) may include Co, Ba, Ti, Sr, Li, La, Zr, Al, etc.

[0087] In one embodiment, the metal oxide particles (20) may not contain nickel. Accordingly, the metal oxide particles (20) do not act as an active material during battery charging and discharging, and thus there is no volume change due to charging and discharging, thereby preventing the gliding phenomenon of the core more efficiently.

[0088] If the metal oxide particles (20) are inorganic materials that do not conduct lithium ions, the portion coated on the surface of the core (10) in the form of a single particle is difficult for lithium to pass through, which may reduce the capacity of the battery or increase the internal resistance of the cell.

[0089] The positive electrode active material according to the present disclosure has metal oxide particles (20) having a structure having lithium ion conductivity, which can prevent a decrease in battery capacity due to coating and also improve the gliding phenomenon of the core (10) having a single particle structure.

[0090] When the metal oxide particles (20) have a spinel crystal structure, they may include, for example, Co3O4, as a compound having a spinel crystal structure or a spinel-like crystal structure.

[0091] When the metal oxide particles (20) have a garnet crystal structure, they may include, for example, LLZO-based compounds as compounds having a garnet crystal structure or a garnet-like crystal structure.

[0092] The above LLZO-based compound may be an oxide containing lithium, lanthanum, and zirconium. The above LLZO-based compound may further include Al, Ga, In, Sc, Ba, Nb, etc. For example, Li7La3Zr2O 12 It may include the back.

[0093] When the metal oxide particles (20) have a nasicon crystal structure, compounds having a nasicon crystal structure or a nasicon-like crystal structure may include, for example, LATP-based compounds, LYZP-based compounds, LAGP-based compounds, etc.

[0094] The above LATP-based compound may be a phosphate containing lithium, aluminum, and titanium. For example, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 may be included.

[0095] The above LYZP-based compound may be a phosphate containing lithium, yttrium, and zirconium. For example, Li 1.3 Y 0.3 Zr 1.7 It may include (PO4)3, etc. The above LAGP-based compound may be a phosphate containing lithium, aluminum, and germanium. For example, Li 1.5 Al 0.5 Ge 1.5 (PO4)3 may be included.

[0096] When the metal oxide particles (20) have a perovskite crystal structure, compounds having a perovskite crystal structure or a perovskite-like crystal structure may include LLTO-based compounds, BaTiO3, SrTiO3, etc.

[0097] The above LLTO-based compound may be an oxide containing lithium, lanthanum, and titanium. For example, Li 0.31 La 0.56 It may include TiO3, etc.

[0098] According to exemplary embodiments, the content of the metal oxide particles may be 500 ppm to 3000 ppm of the total weight of the coated particles. According to some embodiments, the content of the metal oxide particles may be 700 ppm to 1500 ppm or 800 ppm to 1200 ppm of the total weight of the coated particles.

[0099] Within the above range, the gliding phenomenon of the layered structure can be further suppressed, and the capacity of the battery can not be reduced.

[0100] In exemplary embodiments, the content of the coated particles in the total weight of the positive active material may be 50 weight% or more. In some embodiments, the content of the coated particles in the total weight of the positive active material may be 60 weight% or more, 70 weight% or more, 80 weight% or more, or 90 weight% or more. For example, the positive active material may be substantially composed of the coated particles. For example, the positive active material may be composed of the coated particles.

[0101] In some embodiments, the positive electrode active material may further include a lithium cobalt oxide-based active material, a lithium manganese oxide-based active material, a lithium nickel oxide-based active material, a lithium iron phosphate (LFP)-based active material (e.g., LiFePO4), etc.

[0102] In some embodiments, the positive electrode active material may include, for example, a Mn-rich active material, an LLO (Li-rich layered oxide) / OLO (Over-Lithiated Oxide) active material, or a Co-less active material having a chemical structure or crystal structure represented by the following chemical formula 2.

[0103] [Chemical Formula 2]

[0104] p[Li2MnO3]·(1-p)[Li q JO2]

[0105] Of chemical formula 2, 0 <p<1이고, 0.9≤q≤1.2이며, J는 Mn, Ni, Co, Fe, Cr, V, Cu, Zn, Ti, Al, Mg 및 B 중 적어도 하나의 원소를 포함할 수 있다.

[0106] According to exemplary embodiments, a method for manufacturing the positive electrode active material for the secondary battery may be provided. For example, the positive electrode active material for the secondary battery may be manufactured in the following manner, but is not limited thereto.

[0107] According to exemplary embodiments, core particles comprising lithium nickel metal oxide having a layered structure and metal oxide particles can be mixed. The mixing may be dry or wet mixing.

[0108] The coated particles can be produced by heat-treating the mixture prepared by the above mixture. For example, the coated particles can be produced by heat-treating the mixture under conditions of 500°C to 750°C.

[0109] For example, the above heat treatment can be performed in an oxygen atmosphere.

[0110] For example, the heat treatment can be performed for 2 to 5 hours within the temperature range.

[0111] A slurry can be prepared by mixing and stirring the above-mentioned positive active material for a secondary battery with a binder, a conductive material and / or a dispersant, etc., in a solvent. A positive electrode can be manufactured by coating the slurry onto a positive current collector, followed by drying and rolling.

[0112] The above binder may include, for example, organic binders such as vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidenefluoride (PVDF), polyacrylonitrile, and polymethylmethacrylate, or water-based binders such as styrene-butadiene rubber (SBR), and may be used together with a thickener such as carboxymethyl cellulose (CMC).

[0113] For example, a PVDF-based binder can be used as the anode binder. In this case, the amount of binder required to form the anode active material layer can be reduced, and the amount of the anode active material can be relatively increased, thereby improving the output and capacity of the secondary battery.

[0114] The above conductive material may be included to promote electron transfer between active material particles. For example, the conductive material may include carbon-based conductive materials such as graphite, carbon black, graphene, carbon nanotubes, etc., and / or metal-based conductive materials such as perovskite materials such as tin, tin oxide, titanium oxide, LaSrCoO3, LaSrMnO3, etc.

[0115] The above solvent may include, for example, N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, N,N-dimethylaminopropylamine, ethylene oxide, tetrahydrofuran, etc.

[0116] The cathode (130) may include a cathode current collector (125) and a cathode active material layer (120) formed by coating a cathode active material onto the cathode current collector (125). Optionally, it may include a cathode binder and a conductive material.

[0117] For example, the above-mentioned negative electrode active material may be any material known in the art capable of absorbing and extracting lithium ions, without any particular limitation. Examples may include carbon-based materials such as crystalline carbon, amorphous carbon, carbon composites, and carbon fibers; lithium alloys; silicon (Si)-based compounds; or tin. Examples of the above-mentioned amorphous carbon include hard carbon, coke, mesocarbon microbeads (MCMB), and mesophase pitch-based carbon fibers (MPCF).

[0118] Examples of the above-mentioned crystalline carbon include graphite-based carbons such as natural graphite, artificial graphite, graphitized coke, graphitized MCMB, and graphitized MPCF. Examples of elements included in the above-mentioned lithium alloy include aluminum, zinc, bismuth, cadmium, antimony, silicon, lead, tin, gallium, or indium.

[0119] The above silicon-based compound may include, for example, silicon, silicon oxide, or silicon carbide (SiC) and other silicon-carbon composite compounds.

[0120] In some embodiments, the content of silicon active material in the total weight of the negative electrode active material may be 1 to 20 weight%, 1 to 15 weight%, or 1 to 10 weight%.

[0121] A slurry can be prepared by mixing and stirring the above-mentioned negative electrode active material with a binder, a conductive material and / or a dispersant, etc., in a solvent. After coating the above-mentioned slurry onto a negative electrode current collector (125), a negative electrode active material layer (120) can be prepared by drying and compressing.

[0122] For example, a cathode slurry can be prepared by mixing the cathode active material in a solvent. A cathode active material layer (120) can be prepared by coating / depositing the cathode slurry onto a cathode current collector, followed by drying and rolling. The coating process may be carried out using methods such as gravure coating, slot die coating, multilayer simultaneous die coating, imprinting, doctor blade coating, dip coating, bar coating, and casting, but is not limited thereto. The cathode active material layer (120) may further include a binder and optionally further include a conductive material, a thickener, etc.

[0123] Non-limiting examples of the above solvents include water, pure water, deionized water, distilled water, ethanol, isopropanol, methanol, acetone, n-propanol, t-butanol, etc.

[0124] The above-described materials that can be used in the manufacture of the anode as the binder, conductive material, and thickener may be used.

[0125] In some embodiments, styrene-butadiene rubber (SBR) based binder, carboxymethyl cellulose (CMC), polyacrylic acid based binder, poly(3,4-ethylenedioxythiophene), PEDOT based binder, etc. may be used as the cathode binder.

[0126] A separator (140) may be interposed between the anode (100) and the cathode (130). The separator (140) may include a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, an ethylene / methacrylate copolymer, etc. The separator (140) may also include a nonwoven fabric formed of high-melting-point glass fibers, polyethylene terephthalate fibers, etc.

[0127] In some embodiments, the area (e.g., the contact area with the separator (140)) and / or volume of the negative electrode (130) may be larger than that of the positive electrode (100). Accordingly, lithium ions generated from the positive electrode (100) can be smoothly transferred to the negative electrode (130) without precipitating, for example, in the middle.

[0128] According to exemplary embodiments, an electrode cell is defined by an anode (100), a cathode (130), and a separator (140), and a plurality of electrode cells may be stacked to form, for example, an electrode assembly (150) in the form of a jelly roll. For example, the electrode assembly (150) may be formed by winding, laminating, folding, etc., of the separator (140).

[0129] A lithium secondary battery can be defined by housing an electrode assembly (150) in a case (160) together with a non-aqueous electrolyte according to the exemplary embodiments described above. According to the exemplary embodiments, a non-aqueous electrolyte may be used as the electrolyte.

[0130] The non-aqueous electrolyte comprises a lithium salt as an electrolyte and an organic solvent, and the lithium salt is, for example, Li + X - It is expressed as and the anion (X) of the above lithium salt - As F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - Examples of the back can be given.

[0131] Examples of the above organic solvents may include propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethylmethyl carbonate (EMC), methylpropyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, gamma-butyrolactone, propylene sulfite, and tetrahydrofuran. These may be used individually or in combination of two or more.

[0132] As illustrated in FIG. 1, electrode tabs (positive tabs and negative tabs) may protrude from the positive current collector (105) and negative current collector (125) belonging to each electrode cell, respectively, and extend to one side of the case (160). The electrode tabs may be fused together with the one side of the case (160) to form electrode leads (positive lead (107) and negative lead (127)) that extend or are exposed to the outside of the case (160).

[0133] The above lithium secondary battery can be manufactured in, for example, a cylindrical, prismatic, pouch, or coin type using a can.

[0134] In the lithium secondary battery of the present disclosure, the gliding step of the positive electrode is 20 nm or less. The gliding step may be a value that quantitatively represents the amount of gliding generated on the surface of the positive electrode after repeated charging and discharging of the lithium secondary battery.

[0135] The above gliding step is calculated from a line scan graph obtained using an atomic force microscope (AFM) of the anode surface in a completely discharged state after 500 cycles of charging and discharging of the lithium secondary battery.

[0136] For example, the positive electrode can be separated in a fully discharged state (e.g., SOC 0%) after repeated charging and discharging of a lithium secondary battery. The surface of the positive electrode after repeated charging and discharging can be observed and analyzed using an atomic force microscope. Any surface area of ​​the surface of the positive electrode active material layer of the positive electrode can be observed and analyzed using an atomic force microscope.

[0137] When charging and discharging of a battery containing a positive electrode active material comprising lithium metal oxide is repeated, damage such as cracks may occur around the area where gliding phenomena occur. Consequently, the layered structure may irreversibly change into a rock salt structure. Furthermore, repeated charging and discharging may increase the gliding distance and further degrade the performance of the battery.

[0138] In the lithium secondary battery according to the present disclosure, gliding can be suppressed even during repeated charging and discharging. Accordingly, the formation of irregularities on the surface of the positive active material layer can be reduced, and the gliding step can be 20 nm or less. Accordingly, the lifespan characteristics of the battery can be improved.

[0139] According to exemplary embodiments, the 500 charge-discharge cycles may be performed by repeating the charge-discharge of the lithium secondary battery 500 times, charging it to a voltage of 4.3 V to 4.5 V and discharging it to a voltage of 4.2 V. For example, the charging may be performed at 0.3 C CC / CV (0.05 C cutoff) to 4.3 V to 4.5 V, and the discharging may be performed at 0.3 C to a voltage of 2.5 V. The 500 charge-discharge cycles may be performed at a temperature of 30 ℃ to 60 ℃, for example, about 45 ℃.

[0140] The formation charge-discharge cycles may not be counted in the above 500 charge-discharge cycles. For example, a gliding step difference can be calculated for the positive electrode obtained by repeating 500 charge-discharge cycles after the formation charge-discharge of the battery.

[0141] The above line scan can be performed as a straight line perpendicular to the longitudinal direction of the gliding observed with an atomic force microscope. Accordingly, the largest irregular shape can be observed.

[0142] Based on the above line scan, the step difference caused by irregularities on the surface of the positive active material layer can be measured. From this, a graph of the step difference according to the line scan length can be obtained as a line scan graph.

[0143] Multiple line scan graphs may be obtained. In any given line scan graph, a sufficient number of measurement targets may not be observed, and for the reliability of the data, multiple line scan graphs may be obtained by performing multiple line scans in different arbitrary areas on the anode surface after the aforementioned formation charge / discharge.

[0144] Mountain shapes can be observed in the above line scan graph. Each mountain shape is a protruding part of the irregularity and may be a deformation of the anode active material caused by a change in crystal structure resulting from the gliding phenomenon.

[0145] A pair of parallel lines that may include two or more of the mountain shapes between them may be shown in the line scan graph above. The upper line of the parallel lines may be a straight line connecting the crest points of some of the mountain shapes, or it may be any straight line tangent to the mountain shapes.

[0146] The above pair of parallel lines may include another straight line parallel to the said straight line. The said other straight line may be tangent to a valley point of some of the said mountain shapes.

[0147] Two or more of the mountain shapes are included between the pair of parallel lines. For example, at least two of the mountain shapes may be included between the pair of parallel lines, and the rest may be outside the pair of parallel lines.

[0148] The slope of the above parallel lines is not zero. For example, the above parallel lines may not be horizontal or perpendicular to the axis.

[0149] The gliding step is defined as the distance between the pair of parallel lines. By drawing an arbitrary straight line perpendicular to the pair of parallel lines, the distance between the two points where the line intersects the pair of parallel lines can be defined as the gliding step.

[0150] The gliding step of the anode is 20 nm or less. According to some embodiments, the gliding step of the anode may be 10 nm or less.

[0151] If the above gliding step is greater than 20 nm, excessive irreversible gliding may occur during repeated charging and discharging of the battery, which may degrade the battery's lifespan characteristics, and by-products generated due to excessive side reactions with the electrolyte at the gliding point may act as resistance, thereby increasing the internal resistance of the battery.

[0152] According to exemplary embodiments, the lithium secondary battery may have a driving voltage of 4.3 V to 4.7 V. According to some embodiments, the lithium secondary battery may have a driving voltage of 4.3 V to 4.5 V. Accordingly, the battery may be operated in a high voltage region.

[0153] In the following, embodiments of the present disclosure are further described with reference to specific experimental examples. The embodiments and comparative examples included in the experimental examples are merely illustrative of the present disclosure and are not intended to limit the appended claims. It is obvious to those skilled in the art that various changes and modifications to the embodiments are possible within the scope and spirit of the present disclosure, and that such variations and modifications fall within the scope of the appended claims.

[0155] Preparation Example: Preparation of Preliminary Lithium-Nickel Metal Oxide Particles

[0156] NiSO4, CoSO4, and MnSO4 were added and mixed in a molar ratio of 88:9:3 to distilled water from which internal dissolved oxygen had been removed by bubbling with N2 for 24 hours. The above mixture was introduced into a reactor at 50 ℃, and a co-precipitation reaction was carried out for 48 hours using NaOH and NH4OH as a precipitating agent and a chelating agent, respectively, to produce Ni with an average particle size of 3 μm as a transition metal precursor 0.88 Co 0.09 Mn 0.03 A (OH)2 precursor was obtained. The obtained precursor was dried at 80°C for 12 hours, and then re-dried at 110°C for 12 hours.

[0157] Lithium hydroxide and the transition metal precursor were added to a dry high-speed mixer in a ratio of 1.03:1 and mixed uniformly for 5 minutes. The mixture was placed in a calcination furnace under an oxygen atmosphere and heated to 820 °C at a heating rate of 2 °C / min, followed by a first calcination at 820 °C for 10 hours. During heating and calcination, oxygen was continuously passed through at a flow rate of 20 L / min. After the calcination was completed, natural cooling to room temperature was performed, followed by jet-mill grinding and classification to produce LiNi 0.88 Co 0.09 Mn 0.03 Preliminary lithium-nickel metal oxide particles with a single-particle structure denoted by O2 (average particle size (D 50 ): 3 µm) was obtained.

[0159] Example 1

[0160] Manufacturing of positive electrode active materials

[0161] A mixture was prepared comprising the pre-lithium-nickel metal oxide particles of the preparation example and spinel-structured Co3O4 particles having an average particle size (D50) of 250 nm. The mixture was formulated so that the content of Co3O4 particles in the coated particles was 1000 ppm. The mixture was heat-treated in an oxygen atmosphere at a temperature of 750 °C for 120 minutes to produce coated particles.

[0162] Figure 6 is a scanning electron microscope (SEM) image of the coated particles of Example 1.

[0164] Battery manufacturing

[0165] An anode slurry was prepared by mixing the above-mentioned coated particles, polyvinylidene fluoride (PVDF) as a binder, and carbon black as a conductive material in a weight ratio of 96:2:2, respectively. The anode slurry was uniformly applied onto an aluminum foil (12 μm thick), dried, and then rolled to obtain 12 mg / cm² 2 An anode was manufactured by forming an anode active material layer having an areal density of 35 μm and a thickness of 35 μm.

[0166] Artificial graphite and natural graphite as cathode active materials, styrene-butadiene rubber as a binder, and carboxymethylcellulose as a thickener were mixed in a weight ratio of 96:2:2 and then dispersed in water to prepare a cathode active material slurry. This slurry was coated onto a copper foil with a thickness of 8 μm, and then dried and rolled to produce a cathode.

[0167] A 2Ah lithium secondary battery was manufactured by stacking a polyethylene (PE) film separator with a thickness of 13 μm between the electrodes manufactured above, forming a cell using a pouch with dimensions of 5 mm in thickness x 50 mm in width x 60 mm in length, and injecting a non-aqueous electrolyte. As the non-aqueous electrolyte, a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 25:75 was used, in which LiPF6 was dissolved at a concentration of 1 M.

[0169] Example 2

[0170] A positive electrode active material and a battery were prepared in the same manner as in Example 1, except that BaTiO3 particles of a perovskite structure with an average particle size (D50) of 230 nm were used instead of Co3O4 particles.

[0172] Example 3

[0173] A positive electrode active material and a battery were prepared in the same manner as in Example 1, except that BaTiO3 particles of a perovskite structure having an average particle size (D50) of 300 nm were used instead of Co3O4 particles.

[0175] Example 4

[0176] A positive electrode active material and a battery were prepared in the same manner as in Example 1, except that SrTiO3 particles of a perovskite structure having an average particle size (D50) of 250 nm were used instead of Co3O4 particles.

[0178] Example 5

[0179] Li7La3Zr2O with a garnet structure having an average particle size (D50) of 220 nm instead of Co3O4 particles 12 A positive electrode active material and a battery were prepared in the same manner as in Example 1, except that particles were used.

[0181] Example 6

[0182] Li of a nasicon structure having an average particle size (D50) of 250 nm instead of Co3O4 particles 1.3 Al 0.3 Ti 1.7 A positive electrode active material and a battery were prepared in the same manner as in Example 1, except that (PO4)3 particles were used.

[0184] Comparative Example 1

[0185] LiNi 0.88 Co 0.09 Mn 0.03 A battery was manufactured in the same manner as in Example 1, except that a single-particle structured core (D50: 3㎛) having an O2 composition was used as the positive active material.

[0187] Comparative Example 2

[0188] A positive electrode active material and a battery were prepared in the same manner as in Example 1, except that spinel structured Co3O4 particles having an average particle size (D50) of 20 nm were used.

[0189] Figure 7 is a scanning electron microscope (SEM) image of the coated particles of Comparative Example 2.

[0191] Comparative Example 3

[0192] A positive electrode active material and a battery were prepared in the same manner as in Example 1, except that spinel structured Co3O4 particles having an average particle size (D50) of 80 nm were used.

[0194] Comparative Example 4

[0195] A positive electrode active material and a battery were prepared in the same manner as in Example 1, except that spinel structured Co3O4 particles having an average particle size (D50) of 500 nm were used.

[0197] Comparative Example 5

[0198] Li7La3Zr2O with a garnet structure having an average particle size (D50) of 220 nm in the process of mixing lithium hydroxide and the transition metal precursor 12 A positive electrode active material was prepared in the same manner as in the preparation example, except that the particles were additionally mixed to a content of 2000 ppm and calcined. After calcination, a shell with a thickness of about 20 nm was formed on the surface of a core containing lithium metal oxide.

[0199] A positive electrode active material and a battery were prepared in the same manner as in Example 1, except that the above positive electrode active material was used.

[0201] Comparative Example 6

[0202] Li7La3Zr2O among the coated particles 12A positive electrode active material was prepared using the same method as Comparative Example 5, except that the mixture was prepared by formulating it to have a content of 5000 ppm. At this time, a shell with a thickness of about 100 nm was formed on the surface of a core containing lithium metal oxide.

[0203] A positive electrode active material and a battery were prepared in the same manner as in Example 1, except that the above positive electrode active material was used.

[0205] coating Coating type (D50) Standard (nm) Coating composition Coating crystal structure Content (ppm) Example 1 Particle Island type 250 Co3O4 Spinel 1000 Example 2 Particle Island type 230 BaTiO3 perovskite 1000 Example 3 Particle Island type 300 BaTiO3 perovskite 1000 Example 4 Particle Island type 250 SrTiO3 perovskite 1000 Example 5 Particle Island type 220 Li7La3Zr2O 12 Garnet 1000 Example 6 Particle Island type 250 Li 1.3 Al 0.3 Ti 1.7 (PO4)3 Nasicon 1000 Comparative Example 1 - - - - - Comparative Example 2 Particle Island type 20 Co3O4 Spinel 1000 Comparative Example 3 Particle Island type 80 Co3O4 Spinel 1000 Comparative Example 4 Particle Island type 500 Co3O4 Spinel 1000 Comparative Example 5 shell 20 Li7La3Zr2O 12 Garnet 2000 Comparative Example 6 shell 100 Li7La3Zr2O 12 Garnet 5000

[0207] Referring to FIGS. 6 and FIGS. 7, it can be seen that the coated particles of Example 1 contain large-diameter metal oxide particles arranged in an island shape on the core surface, and the coated particles of Comparative Example 2 contain small-diameter metal oxide particles on the core surface.

[0209] Reference Example

[0210] LiNi 0.88 Co 0.09 Mn 0.03 A battery was manufactured using the same method as the above battery manufacturing, except that a lithium nickel metal oxide with a single particle structure having an O2 composition and BaTiO3 particles with a perovskite structure having an average particle size (D50) of 230 nm were mixed to have a content of 1000 ppm and used as the positive active material.

[0212] Experimental Example

[0213] The electrochemical characteristics and physical properties of the batteries of the above examples and comparative examples were evaluated by the following method and are shown in Table 2.

[0214] (1) Evaluation of the initial discharge capacity of the battery

[0215] In the batteries of the examples and comparative examples, the battery was charged at room temperature (25°C) with a constant current (CC) of 0.1 C until the voltage reached 4.3 V, and then charged once with a constant voltage (CV) of 4.3 V until the charging current reached 0.05 C. After leaving it for 10 minutes, the battery was discharged once with a constant current of 0.1 C until the voltage reached 3.0 V to measure the discharge capacity.

[0216] (2) Evaluation of battery life characteristics

[0217] In the batteries of the examples and comparative examples, charging (CC-CV, 0.5C 4.4V) and discharging (1.0 C 3.0V) at 4.3 V at a high temperature (45℃) were repeated 500 times (cycle), and the capacity retention rate during the life characteristic evaluation was measured according to the following formula. The capacity retention rate was calculated as the ratio of the discharge capacity after 500 cycles to the initial discharge capacity of (1).

[0218] Capacity retention rate (%) after 500 cycles = {(Discharge capacity after 500 cycles (mAh / g)) / (Initial discharge capacity (mAh / g))} x 100

[0219] (3) Evaluation of gliding phenomenon occurrence

[0220] After repeating 500 cycles of (1), the battery was completely discharged at a constant current of 0.1 C until it reached 3.0 V, after which the positive electrode was separated from the battery, and the surface of the positive electrode active material layer was observed using an Atomic Force Microscope. Specifically, using an AFM analysis instrument (ICON, Bruker), a surface image of the positive electrode active material layer was captured in a 5 μm x 5 μm area using a probe with a spring constant of 42 N / m at a resolution of 1024 x 1024 and a speed of 0.5 Hz, and line scanning was performed. Parallel lines were plotted so that at least two peak shapes were included in the step difference graph resulting from the line scanning, and the spacing between the parallel lines was measured.

[0221] Figure 8a is an AFM image of the anode after repeated charge and discharge of Example 2.

[0222] FIG. 8b is a step difference graph according to line scanning of the anode after repeated charge and discharge of Example 2, scanned along the dotted line of FIG. 8a.

[0223] Figure 9a is an AFM image of the anode after repeated charge and discharge of Comparative Example 2.

[0224] Figure 9b is a step difference graph according to line scanning of the anode after repeated charge and discharge of Comparative Example 2, scanned along the solid line of Figure 9a.

[0225] Initial discharge capacity (mAh / g) Capacity retention rate (%) Average step difference (nm) Example 1 215.3 87.3 7.3 Example 2 216.2 87.3 8.3 Example 3 215.5 86.2 7.8 Example 4 215.1 86.9 8.8 Example 5 216.1 88.1 8.5 Example 6 216.2 88.5 9.1 Comparative Example 1 218.0 70 35.1 Comparative Example 2 216.9 81.5 24.1 Comparative Example 3 216.5 80.1 21.3 Comparative Example 4 210 78.5 - Comparative Example 5 216.5 85 20.1 Comparative Example 6 208.5 - - Reference Example 218.0 70 35.3

[0227] Referring to Table 2 above, the batteries of the examples had a high initial discharge capacity and maintained a high capacity after repeated charge and discharge. In addition, the occurrence of layered structure gliding phenomena of the single-particle core was suppressed, and the average step difference was observed to be 10 nm or less.

[0228] Referring to FIGS. 8a to 9b, in the positive electrode active material of Example 2, gliding was suppressed even during repeated charging and discharging, and only a small step of about 8.3 nm was formed. On the other hand, in the positive electrode active material of Comparative Example 2, the metal oxide having a particle size of less than 100 nm failed to suppress gliding, and a step of about 24 nm was formed.

[0229] On the other hand, in Comparative Example 1 and Reference Example, in which a cathode was manufactured using a single-particle structure lithium nickel metal oxide without a coating, excessive gliding of the layered structure occurred, and the average step difference exceeded 30 nm, resulting in significant deterioration of the battery's life characteristics.

[0230] In Comparative Examples 2 and 3, which used a positive electrode active material coated with metal oxide particles having a particle size of less than 100 nm, the gliding phenomenon of the layered structure was not effectively suppressed.

[0231] In Comparative Example 4, which used a positive active material coated with metal oxide particles having a particle size greater than 450 nm, the density of the positive active material in the positive active material layer may be reduced, and the portion coated with large-sized metal oxide particles may act as a resistance during lithium insertion and / or extraction, resulting in a slight decrease in the initial discharge capacity of the battery. Additionally, the lifespan characteristics of the battery were partially degraded.

[0232] In Comparative Example 5, which used a positive electrode active material having a shell-shaped coating rather than an island-shaped particle arrangement, the gliding phenomenon of the layered structure was not effectively suppressed. In particular, in Comparative Example 6, which used a positive electrode active material having a thicker shell-shaped coating, the initial discharge capacity of the battery was significantly reduced as the content of the metal oxide was too high and the content of the lithium nickel metal oxide was relatively lowered.

[0233] The above description is merely an example of applying the principles of the present disclosure, and other configurations may be included without departing from the scope of the present disclosure. Explanation of the symbols

[0235] 10: Core 20: Metal oxide particles 100: Anode 105: Anode current collector 107: Anode Lead 110: Anode Active Material Layer 120: Cathode active material layer 125: Cathode current collector 127: Cathode Lead 130: Cathode 140: Separator 150: Electrode assembly 160: Case

Claims

Claim 1 A lithium secondary battery comprising: a positive electrode; and a negative electrode facing the positive electrode, wherein the gliding step of the positive electrode is 20 nm or less, and the gliding step is defined as the distance between a pair of parallel lines with a non-zero slope that may include two or more of the peak shapes observed in a line scan graph obtained using an atomic force microscope (AFM) of the surface of the positive electrode in a fully discharged state after 500 charge-discharge cycles of the battery. Claim 2 A lithium secondary battery according to claim 1, wherein the gliding step of the positive electrode is 10 nm or less. Claim 3 A lithium secondary battery according to claim 1, wherein the positive electrode comprises a positive electrode current collector and a positive electrode active material layer disposed on one surface of the positive electrode current collector, the positive electrode active material layer comprises coated particles, the coated particles comprise a lithium nickel metal oxide having a layered structure and a core having a single particle structure; and at least one metal oxide particle disposed on the surface of the core. Claim 4 A lithium secondary battery according to claim 3, wherein the average particle size (D50) of the metal oxide particles is 100 nm to 450 nm. Claim 5 A lithium secondary battery according to paragraph 3, wherein the metal oxide particles are arranged in an island shape on the surface of the core. Claim 6 In paragraph 3, the metal oxide particles have a spinel crystal structure, a perovskite crystal structure, a garnet crystal structure, or a nasicon crystal structure, in a lithium secondary battery. Claim 7 A lithium secondary battery according to claim 3, wherein the metal oxide particles comprise at least one selected from the group consisting of Co, Ba, Ti, Sr, Li, La, Zr, Al, Y, W, and P. Claim 8 A lithium secondary battery according to paragraph 3, wherein the content of the metal oxide particles is 500 ppm to 3000 ppm of the total weight of the coated particles. Claim 9 A lithium secondary battery according to paragraph 3, wherein the nickel content among the total moles of elements excluding lithium and oxygen in the lithium nickel metal oxide is 60 mol% to 99 mol%. Claim 10 A lithium secondary battery according to paragraph 3, wherein the average particle size (D50) of the core is 1 μm to 10 μm. Claim 11 A lithium secondary battery according to paragraph 3, wherein the crystal grain size of the core is 200 nm to 600 nm. Claim 12 In claim 1, the 500 charge-discharge cycles are performed by repeating the charge-discharge cycle 500 times, wherein the lithium secondary battery is charged to a voltage of 4.3 V to 4.5 V and discharged to a voltage of 4.2 V. Claim 13 A lithium secondary battery having a driving voltage of 4.3 V to 4.7 V in claim 1.

Citation Information

Patent Citations

  • High-nickel positive electrode material, preparation method thereof and lithium secondary battery

    CN114512645A

  • Positive electrode material for lithium ion battery and preparation method therefor, and lithium ion battery

    EP4138160A1

  • Positive electrode material for lithium ion batteries, manufacturing method thereof, and lithium ion battery

    JP2023515899A

  • Positive electrode material for lithium ion battery and preparation method therefor, and lithium ion battery

    US20230122382A1

  • Cathode material for lithium ion batteries and method for manufacturing the same, and lithium ion batteries

    KR102708961B1